Chimeric Japanese Encephalitis Virus SA14/SA14-14-2 Was Virulence Attenuated and Protected the Challenge of Wild-Type Strain SA14. (3rd March 2019) - Huang, Rong; Leng, Shengling; Feng, Yalan; Tang, Liping; Yuan, Lei; Yang, Jian
Abstract : The attenuated Japanese encephalitis virus (JEV) live vaccine SA14-14-2 prepared from wild-type (WT) strain SA14 was licensed to prevent Japanese encephalitis (JE) in 1989 in China. Many studies showed that the premembrane (prM) and envelope (E) protein were the crucial determinant of virulence and immunogenicity of JEV. So we are interested in whether the substitution of prM/E of JEV WT SA14 with those of vaccine strain SA14-14-2 could decrease neurovirulence and prevent the challenge of JEV WT SA14. Molecular clone technique was used to replace the prM/E gene of JEV WT strain SA14 with those of vaccine strain SA14-14-2 to construct the infectious clone of chimeric virus (designated JEV SA14/SA14-14-2), the chimeric virus recovered from BHK21 cells upon electrotransfection of RNA into BHK21 cells. The results showed that the recovered chimeric virus was highly attenuated in mice, and a single immunization elicited strong protective immunity in a dose-dependent manner. This study increases our understanding of the molecular mechanisms of neurovirulence attenuation and immunogenicity of JEV.